Answer:
Option 3rd is correct
![a_6 = -1](https://img.qammunity.org/2019/formulas/mathematics/college/fjx6as2f35hlzgbkudwjoqb1tmkybxq3jw.png)
Explanation:
The nth term for the geometric sequence is given by:
![a_n = a_1 \cdot r^(n-1)](https://img.qammunity.org/2019/formulas/mathematics/college/n3srtv9stg5rn29s4ctbu6tib3l5fcb5rd.png)
where,
is the first term
r is the common ratio
n is the number of terms.
As per the statement:
![a_1 = 1024](https://img.qammunity.org/2019/formulas/mathematics/college/p5fltjlz27wlvo07bqiriqla2noaf2on4u.png)
![a_4 = -16](https://img.qammunity.org/2019/formulas/mathematics/college/1ccn29oiijzpwmye3ey8i2g7gx0e4ehxec.png)
For n = 4, we have;
![a_4 = a_1 \cdot r^3](https://img.qammunity.org/2019/formulas/mathematics/college/vxoo6o4lyzrv9r4ftvtj3pasy8fxwrd7ok.png)
⇒
![-16 = 1024 \cdot r^3](https://img.qammunity.org/2019/formulas/mathematics/college/jobmo8ku9zfc5uvyjet7ldmhs0bgnpjb7k.png)
Divide both sides by 1024 we have;
![-(1)/(64) =r^3](https://img.qammunity.org/2019/formulas/mathematics/college/lokbskpfoggqm9a51q5qm0etlzru4griud.png)
⇒
![r =\sqrt[3]{-(1)/(64)}=\sqrt[3]{-(1)/(4^3)}](https://img.qammunity.org/2019/formulas/mathematics/college/enuho265bf8yb5iuxmhojcn22plr3mak8g.png)
⇒
![r = -(1)/(4) = -0.25](https://img.qammunity.org/2019/formulas/mathematics/college/4xq4w7p0iwcmj7geysk4a3mg1hcvqcaq70.png)
We have to find the value of 6th term.
for n = 6
![a_6 = 1024 \cdot (-0.25)^5 = 1024 \cdot (-0.0009765625) = -1](https://img.qammunity.org/2019/formulas/mathematics/college/i710fs6esuuqe4zqylaakh3gk4d102uvrd.png)
⇒
![a_6 = -1](https://img.qammunity.org/2019/formulas/mathematics/college/fjx6as2f35hlzgbkudwjoqb1tmkybxq3jw.png)
Therefore, the 6th term of the geometric sequence is, -1